2017
DOI: 10.1021/acs.jpcc.6b09960
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional C4N Global Minima: Unique Structural Topologies and Nanoelectronic Properties

Abstract: Atomically thin 2D materials have drawn great attention due to their many potential applications. We herein report two novel structures of 2D C4N identified by first-principles calculations in combination with a swarm structure search. These two structures (with symmetry of Pm and P2/m) are almost degenerate in energy (with only 4 meV/atom difference) and exhibit quite similar structural topologies, both consisting of alternative arrays of C–N hexagon and arrays of C–N pentagon–octagon–pentagon. The Pm structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 44 publications
(60 reference statements)
0
32
0
Order By: Relevance
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%
“…These two configurations of C 4 N are semiconductors in nature and display a narrow and zero bandgap (Fig. 4 k); however, this property can be tuned easily [ 24 , 26 ].…”
Section: Cnbmsmentioning
confidence: 99%
“…It exhibits a unique electronic properties such as ballistic charge transport [30], high carrier mobility [31], and quantum Hall effect [32]. Subsequently, many 2D lattices such as germanene [33], carbon allotropes [34][35][36][37], boron allotropes [38], SiC 3 [27], and C 4 N [39], have been identified as Dirac materials. However, the Dirac cone in these materials is intrinsically spin-degenerated, which actually limits its utilization in massless spintronics.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, HDSs can be divided into two types: type-I, the d-state HDSs, in which the Dirac state is contributed by d-orbital of transitional-metal atoms, and type-II, the p-state HDSs, whose states are from p-orbital of transitional-metal atoms. To date, the reported majority of HDS members are belong to type-I HDSs [39][40][41][42][43][44][45][46][47], while there has been barely any on 2D type-II HDS materials. It is highly desirable to design type-II HDSs with robust spin ordering and high Curie temperature simultaneously, which may make the experimental synthesis largely accessible.…”
Section: Introductionmentioning
confidence: 99%